Corn farmers intention towards internet of things (IoT) for agricultural production in Perak - Nurul Aqilah Mohamed Sohaimi (2022)
IoT has a significant impact in agriculture since it has different purposes and offer multiple solutions. Besides, farmers’ intention is the knowledge and behaviour of farmers to adopt new agricultural technology. Corn farmers with strong intentions towards the potential and benefits of IoT are likely endorse farmers’ decisions to adopt the IoT. The main challenge for corn farmers including a lack of knowledge and awareness about IoT causing the farmers to be unable to manage the risk and uncertainties in corn production. Also, corn farmers currently have limited access to private or public extension as well as lack of information related to the use of IoT in agriculture. The sample size is 50 respondents of corn farmer and was conducted in Perak. This study was carried out based on three objectives, which is to determine corn farmers intention towards IoT for agricultural production in Perak. Secondly, to investigate the relationship of attitude, subjective norm and perceived behaviour control of corn farmers intention towards IoT for agricultural production in Perak. Third objective is to identify the most influential factor of corn farmers intention towards IoT for agricultural production in Perak. Next, this study used purposive sampling method where a set of questionnaire survey was distributed among corn farmers in Perak by applying Theory of Planned Behaviour (TPB). The findings from this study are high-level intention of corn farmers towards IoT for agricultural production. Moreover, there is a positive relationship of attitude, subjective norms and perceived behaviour control of corn farmers intention towards IoT for agricultural production in Perak. Meanwhile, the most influential factor of corn farmers intention towards IoT for agricultural production in Perak is attitude. Finally, Confirmatory Factor Analysis showed that the model fit is acceptable.